2018
DOI: 10.1007/s00345-018-2409-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hexanic extract of Serenoa repens on prostatic inflammation: results from a randomized biopsy study

Abstract: HESr seems to reduce prostatic inflammation in terms of histological and immunohistochemical parameters in this specific patients population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 12 publications
0
29
0
8
Order By: Relevance
“…HESr seems to reduce prostatic in lammation in terms of histological and immunohistochemical parameters in this speci ic patients population" [36].…”
Section: Resultsmentioning
confidence: 94%
“…HESr seems to reduce prostatic in lammation in terms of histological and immunohistochemical parameters in this speci ic patients population" [36].…”
Section: Resultsmentioning
confidence: 94%
“…The randomized blinded trial on the effect of HESr on prostatic inflammation is the only trial in humans with two prostatic biopsies on the same patient (at baseline and end of study). It was found that treatment with HESr reduced both extension and aggressiveness of inflammation [9].…”
Section: Discussionmentioning
confidence: 99%
“…This randomized blinded trial included patients with confirmed prostatic inflammation after a transrectal prostate biopsy due to increased prostate-specific antigen (PSA) levels and/or a positive direct rectal examination. The concept and the design of the study were previously described in detail [9]. Briefly, eligible patients were randomized into two groups: Group A, who received hexanic Serenoa repens 320 mg per day for six months, and Group B, who were given no therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl and ethyl esters, % [42]. В другом наблюдении, в ходе полугодового двойного слепого рандомизированного исследования эквивалентности, сравнивали эффект препарата Пермиксон (320 м/день) с эффектом ингибитора 5α-редуктазы (финастерид, 5 мг/день) у 1098 мужчин с умеренной ДГПЖ с использованием шкалы IPSS (International Prostate Symptom Score -Международная шкала оценки простатических симптомов) в качестве основного оценочного критерия.…”
Section: метиловые и этиловые эфиры %unclassified